2014
DOI: 10.1016/j.mmcr.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The case of diagnostics of invasive pulmonary aspergillosis by in vivo probe-based confocal laser endomicroscopy of central and distal airways

Abstract: We present a case of 41-year-old patient with invasive pulmonary aspergillosis (IPA) in which probe-based confocal laser endomicroscopy (pCLE) imaging of central and distal airways was first performed in vivo. pCLE imaging showed the signs of complete or partial destruction of elastin network of alveolar wall with fibrillar branching fluorescent structures in the zone with typical IPA changes on HRCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
1
8
0
2
Order By: Relevance
“…However, there have been 2 pathologic types in which we found the same giant highly fluorescent alveolar macrophages using in vivo pCLE, namely, invasive pulmonary aspergillosis 18 and amiodarone-related pneumonia. 14 Our findings correspond to the findings of Morisse et al 19 who used fibered confocal fluorescence microscopy for in vivo and in situ imaging of experimental invasive pulmonary aspergillosis in immunosuppressed rats; they describe a specific fibrillar fluorescence and local infiltration of fluorescent alveolar macrophages in the infected zones.…”
Section: Discussionsupporting
confidence: 53%
“…However, there have been 2 pathologic types in which we found the same giant highly fluorescent alveolar macrophages using in vivo pCLE, namely, invasive pulmonary aspergillosis 18 and amiodarone-related pneumonia. 14 Our findings correspond to the findings of Morisse et al 19 who used fibered confocal fluorescence microscopy for in vivo and in situ imaging of experimental invasive pulmonary aspergillosis in immunosuppressed rats; they describe a specific fibrillar fluorescence and local infiltration of fluorescent alveolar macrophages in the infected zones.…”
Section: Discussionsupporting
confidence: 53%
“…Previous clinical studies have shown that this approach can successfully be used to investigate the human airways and lungs based on autofluorescence originating from the elastin network 25 28 . To date, applications in the field of fungal lung infections have been limited because of a lack of specific signals originating from the pathogens 29 , 30 . One possible solution to solve the lack of specificity in WT infections is the in vivo use of fluorophores that specifically bind to fungal elements.…”
Section: Discussionmentioning
confidence: 99%
“…Bronchoscopy is a minimally invasive procedure that allows pCLE but can also obtain respiratory secretions and bronchoalveolar lavage allowing their analyses identifying other potential microorganisms. We do not defend the replacement of lesser invasive techniques but we stress a new inclusion of pCLE indication besides pulmonary aspergillosis, alveolar proteinosis, drug pneumonitis and lung cancer [15,16,17,18,38,39]. …”
Section: Discussionmentioning
confidence: 99%